Remediation of a heavy metals contaminated soil using mycorrhized and non‐mycorrhized Helichrysum italicum (Roth) Don. (11th December 2017) - Brunetti, Gennaro; Ruta, Claudia; Traversa, Andreina; D'Ambruoso, Giuseppe; Tarraf, Waed; De Mastro, Francesco; De Mastro, Giuseppe; Cocozza, Claudio
Abstract: Four hundred hectares of the inland and hilly part of Apulia Region (Southern Italy) were contaminated by using low‐quality composts for many years. That territory now belongs to a national park and needs a sustainable soil restoration. Therefore, a greenhouse experiment was carried out to test the phytoremediation potential of the frugal Helichrysum italicum (Roth) Don, alone and mycorrhized by Septoglomus viscosum. The aims of the research were (a) to test if the H .  italicum can reduce the soil content of Cd, Co, Cr, Cu, Ni, Pb, and Zn; (b) to identify in which part of the plant those metals are mainly accumulated; (c) to check the role of S .  viscosum in promoting the plant growth and the soil phytoremediation. The results showed better plant growth in contaminated soils in comparison to control soils, regardless of the presence of mycorrhiza, probably due to the better soil fertility parameters in contaminated soils. In addition, non‐mycorrhized plants from contaminated soil accumulated greater amounts of heavy metals, especially Cr, Cu, Pb, and Zn, in their root system. According to the translocation and bioconcentration factors, the mechanism by which H .  italicum incorporated heavy metals was ascribable to a phytostabilization process. In contrast, the application of mycorrhiza in the contaminated soil reduced the uptake of heavy metals by the roots, possibly through an exclusion mechanism, reducing the phytoremediation potential of H .  italicum .